A natação como auxiliar no desenvolvimento escolar de alunos com Transtorno do Espectro Autista (TEA) - Noviscki, Juliane [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
With changes in the autism nomenclature, the most current term is Autism Spectrum Disorder (ASD), which has clinical characteristics of isolation, with extreme difficulty in establishing links with people or situations, absence of language, refusal of food, sudden movements, repetition of attitudes and manipulation of objects. There is no exam to diagnose the cause; the child neurologist, along with other professionals, identifies the diagnosis. Every child has the right to education in the regular school system, with the expansion of inclusive education teachers are seeking training to meet the demand, and physical education is a link of great importance in this inclusion, since adequate physical activity the possibilities of the subject, values, integrates with reality, obtaining autonomy, self-confidence and freedom. Swimming as an extracurricular activity helps in the development of these children, since water is the facilitating medium, which provokes challenges and allows the child free and independent movements, as well as the playful actions that stimulate the expansion of social interaction, contributing to the organization affective and psychomotor partner of the child. The objective of the study was to identify the behavioral changes in the school of the child with ASD during the participation of a swimming practice program. The results showed that there was an improvement in the behavior, and they emphasized the question of following rules, the responsibility of the students during the classes in the school, as well as the improved socialization, since the child with ASD presented less tense and more motivated in the school, which facilitated their learning

Com alterações da nomenclatura do autismo, o termo mais atual é Transtorno do Espectro Autista (TEA), que tem características clínicas como: isolamento, extrema dificuldade para estabelecer vínculos com pessoas ou situações, ausência de linguagem, seletividade alimentar, movimentos bruscos, repetição de atitudes e manipulação de objetos. Não existe um exame para diagnosticar a causa, quem identifica o diagnóstico é o neurologista infantil, em conjunto com outros profissionais. Toda criança tem direito a educação no sistema escolar regular, com a expansão da educação inclusiva professores estão buscando formação para suprir a demanda, e a educação física é um elo de grande importância nessa inclusão, já que a atividade física adequada as possibilidades do sujeito, valoriza, integra à realidade, obtendo autonomia, autoconfiança e liberdade. A natação como atividade extracurricular vem auxiliar no desenvolvimento destas crianças, já que a água é o meio facilitador, que provoca desafios e possibilita a criança movimentos livres e independentes, bem como as ações lúdicas que estimulam a ampliação da interação social, contribuindo para a organização sócio afetiva e psicomotora da criança. O objetivo do estudo foi identificar as alterações do comportamento na escola da criança com TEA, durante participação de um programa de prática da natação. A partir dos resultados encontrados concluímos que houve uma melhora no comportamento, com ênfase na responsabilidade dos alunos durante as aulas na escola, bem como seguir regras, melhora da socialização, já que a criança com TEA se apresentou menos tensa e mais motivada na escola, o que facilitou o seu aprendizado
Keywords: Autismo; Transtorno do espectro autista; Natação; Escolas; Autism